Konsentrasiekstrakdaunsirsak(Annonamuricata)yangmenghambatpertumbuhan Candida albicans pada lempeng resin akrilik polimerisasi panas Concentration of soursop (Annona muricata)leaf extract in inhibiting Candida albicans on heat cure acrylic resin plate - Bahruddin Thalib; Herawati Hasan (Journal of Dentomaxillofacial Science, 2013)
Soursops (Annona muricata)are plants that have flower and sweet fruit. These plants have been used since long fortraditional medicine, especially the leaves, seeds, and fruits. This study aimed to determine the effect of concentrationof soursop leaf extract to the growth of Candida albicans on heat curing acrylic resin plate. The study begins with themanufacture of soursop leaf extract concentrations of 5%, 15%, 25%, 35%, and 45%, dilution of the extract, thepurification of C.albicans, growing C.albicans on saboraud dextrose agar medium, and minimum inhibitoryconcentration test. Data were analyzed by ANOVA followed by LSD test using SPSS 16.0. The results showed asignificant difference in the average number of C.albicans that grows between each concentration soursop leaf extract(Î±<0.05) and soursop leaf extract at a concentration of 45% is the most effective in inhibiting the growth of C.albicans.It was concluded that the higher the concentration of soursop leaf extract, the more effective in inhibiting the growth ofC.albicans.